Interaction between nematodes and bacteria enhances soil carbon sequestration under organic material amendments - Shi, Guangping; Luan, Lu; Zhu, Guofan; Zeng, Zhaoyang; Zheng, Jie; Shi, Yue; Sun, Bo; Jiang, Yuji (Frontiers in Microbiology, 2023)
The process of carbon (C) sequestration plays an important role in soil fertility and productivity, yet most studies have focused on the individual role of the bacterial community. However, an in-depth mechanistic understanding of how soil nematodes interact with the bacterial community to regulate soil C accumulation is still lacking. We conducted a 10-year field experiment to explore the nematode and bacterial communities and determine the influence of nematode-bacteria interactions on C mineralization, microbial metabolic quotient (qCO2), and carbon use efficiency (CUE) under the organic material amendments, including chemical fertilizers with straw (NS), chemical fertilizers with straw and pig manure (NSM), and chemical fertilizer with straw biochar (NB). Here, our results showed the abundance of bacterial and nematode communities was significantly higher under NS, NSM, and NB treatments than under chemical fertilizers (N) treatment, with the highest abundance under the NSM treatment. The enrichment index and functional dispersion index were significantly higher under NSM treatment than under N, NS, and NB treatments, while the channel index followed the opposite pattern. Structural equation modeling indicated that the potential predation pressure induced by nematodes may improve bacterial abundance, with positive cascading effects on C sequestration. Collectively, our study highlights the functional importance of nematode-microorganism interactions in mediating C dynamics under organic material amendments.